A Study of Literature for Readers And Critics - Daiches, David (New York W-W-Norton and Company-INC, 1964)
"Why do we spend time readingand discussing books which never in fact occured?" The question is elementary and yet, as David Daiches suggest in this provocative study, it is the elementary that are never answered. Although literary criticism today is more concerned with technique than with the basic question of value, the question of value underlies all others. Professor Daiches therefore directs this book to the search for the basic funtion and purpose of imaginative prose and poetry.
Keywords: Literature